Cut Cube Surface Area

Geometry Level 5

A unit cube is to be cut by a plane defined by three points that it passes through. The cube faces are parallel to the coordinate planes, with one vertex at the origin and the opposing vertex at ( 1 , 1 , 1 ) (1,1,1) . The cutting plane passes through the points ( 0.5 , 0 , 1 ) , ( 0 , 0.5 , 1 ) (0.5, 0, 1) , (0, 0.5, 1) and ( 1 , 1 , 0.5 ) (1, 1, 0.5) . Find the total surface area of the portion of the cube that will separate upward when the cut is complete (the upper part of the cube).

If this area can be expressed as a + b c d \dfrac{a + b \sqrt{c}}{d} , for coprime integers a a , b b and d d , and square-free integer c c , then find a + b + c + d a + b + c + d


The answer is 81.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Sep 13, 2020

Label the cube as shown. If we look along E C E'C' , we note that A E E \triangle AEE' and A D D \triangle ADD' are similar. Then E E D D = A E A D E E = A E A D × D D = 1 3 × 1 2 = 1 6 \frac {EE'}{DD'} = \frac {AE'}{AD'} \implies EE' = \frac {AE'}{AD'} \times DD' = \frac 13 \times \frac 12 = \frac 16 . Then we have C ( 0 , 1 , 5 6 ) C \left(0,1,\frac 56\right) and E ( 1 , 0 , 5 6 ) E\left(1,0,\frac 56\right) . The the cut out surface is a pentagon A B C D E ABCDE of the shape of a cut diamond.

We can find the side lengths using the coordinates of the end points by = ( x 1 x 2 ) 2 + ( y 1 y 2 ) 2 + ( z 1 z 2 ) 2 \ell = \sqrt{(x_1-x_2)^2+(y_1-y_2)^2+(z_1-z_2)^2} . And they are A B = 1 2 AB=\frac 1{\sqrt 2} , B C = E A = 10 6 BC=EA = \frac {\sqrt{10}}6 , C D = D E = 10 3 CD=DE=\frac {\sqrt{10}}3 , and C E = 2 CE=\sqrt 2 . We note that the are of the pentagon [ A B C D E ] [ABCDE] is the of areas of trapezoid A B C E ABCE and C D E \triangle CDE . From the side view along E C EC , we note that the height of A B C E ABCE , h 1 h_1 , and the height of C D E \triangle CDE , h 2 h_2 , are h 1 : h 2 = 1 : 2 h_1:h_2 = 1:2 . And h 1 + h 2 = ( 3 4 2 ) 2 + ( 1 2 ) 2 = 11 2 2 h_1+h_2 = \sqrt{\left(\frac 34\sqrt 2\right)^2+\left(\frac 12\right)^2} = \frac {\sqrt{11}}{2\sqrt 2} . h 1 = 11 6 2 \implies h_1 = \frac {\sqrt{11}}{6\sqrt 2} and h 2 = 11 3 2 h_2 = \frac {\sqrt{11}}{3\sqrt 2} . Then the area of pentagon A B C D E ABCDE is given by:

[ A B C D E ] = [ A B C E ] + [ C D E ] = A B + C E 2 × h 1 + C E 2 × h 2 = 1 2 ( 1 2 + 2 ) 11 6 2 + 1 2 × 2 × 11 3 2 = 11 8 + 11 6 = 7 11 24 \begin{aligned} [ABCDE] & = [ABCE] + [CDE] \\ & = \frac {AB+CE}2 \times h_1 + \frac {CE}2 \times h_2 \\ & = \frac 12 \left(\frac 1{\sqrt 2} + \sqrt 2\right)\frac {\sqrt{11}}{6\sqrt 2} + \frac 12 \times \sqrt 2\times \frac {\sqrt{11}}{3\sqrt 2} \\ & = \frac {\sqrt{11}}8 + \frac {\sqrt{11}}6 = \frac {7\sqrt{11}}{24} \end{aligned}

Other surface areas of the top part of the cube are:

[ A B C D E ] = 1 × 1 1 2 × 1 2 × 1 2 = 7 8 2 [ A E E ] = 2 × 1 2 × 1 2 × 1 6 = 1 12 2 [ E E D D ] = 2 × 1 6 + 1 2 2 × 1 = 2 3 \begin{aligned} [ABC'D'E'] & = 1 \times 1 - \frac 12 \times \frac 12 \times \frac 12 = \frac 78 \\ 2[AEE'] & = 2\times \frac 12 \times \frac 12 \times \frac 16 = \frac 1{12} \\ 2[E'EDD'] & = 2 \times \frac {\frac 16 + \frac 12}2 \times 1 = \frac 23 \end{aligned}

Therefore the surface area of the top part of the cube is 7 11 24 + 7 8 + 1 12 + 2 3 = 39 + 7 11 24 \dfrac {7\sqrt{11}}{24} + \dfrac 78 + \dfrac 1{12} + \dfrac 23 = \dfrac {39+7\sqrt{11}}{24} . a + b + c + d = 39 + 7 + 11 + 24 = 81 \implies a + b + c + d = 39+7+11+24 = \boxed {81} .

David Vreken
Sep 12, 2020

Label the diagram as follows:

The plane has an equation of x + b y + c z = d x + by + cz = d , and since it goes through A ( 0 , 1 2 , 1 ) A(0, \frac{1}{2}, 1) , B ( 1 2 , 0 , 1 ) B(\frac{1}{2}, 0, 1) , C ( 1 , 1 , 1 2 ) C(1, 1, \frac{1}{2}) , we know that 0 + 1 2 b + c = d 0 + \frac{1}{2}b + c = d , 1 2 + 0 + c = d \frac{1}{2} + 0 + c = d , and 1 + b + 1 2 c = d 1 + b + \frac{1}{2}c = d , which solves to b = 1 b = 1 , c = 3 c = 3 , and d = 7 2 d = \frac{7}{2} , and gives an equation of x + y + 3 z = 7 2 x + y + 3z = \frac{7}{2} or 2 x + 2 y + 6 z = 7 2x + 2y + 6z = 7 .

G G is also on the plane 2 x + 2 y + 6 z = 7 2x + 2y + 6z = 7 with x = 1 x = 1 and y = 0 y = 0 , so its coordinates solve to ( 1 , 0 , 5 6 ) (1, 0, \frac{5}{6}) , which means E G = 1 5 6 = 1 6 EG = 1 - \frac{5}{6} = \frac{1}{6} .

The area of B E G \triangle BEG is A B E G = 1 2 B E E G = 1 2 1 2 1 6 = 1 24 A_{\triangle BEG} = \frac{1}{2} \cdot BE \cdot EG = \frac{1}{2} \cdot \frac{1}{2} \cdot \frac{1}{6} = \frac{1}{24} . By symmetry, A A D F = A B E G = 1 24 A_{\triangle ADF} = A_{\triangle BEG} = \frac{1}{24} .

The area of trapezoid E H C G EHCG is A E H C G = 1 2 ( E G + H C ) E H = 1 2 ( 1 6 + 1 2 ) 1 = 1 3 A_{EHCG} = \frac{1}{2}(EG + HC)EH = \frac{1}{2}(\frac{1}{6} + \frac{1}{2})1 = \frac{1}{3} . By symmetry, A D H C F = A E H C G = 1 3 A_{DHCF} = A_{EHCG} = \frac{1}{3} .

The area of E D H \triangle EDH is A E D H = 1 2 E H D H = 1 2 1 1 = 1 2 A_{\triangle EDH} = \frac{1}{2} \cdot EH \cdot DH = \frac{1}{2} \cdot 1 \cdot 1 = \frac{1}{2} .

By the Pythagorean Theorem, the height of trapezoid A D E B ADEB is h 1 = B E 2 ( 1 2 ( D E A B ) ) 2 = ( 1 2 ) 2 ( 1 2 ( 2 2 2 ) ) 2 = 2 4 h_1 = \sqrt{BE^2 - (\frac{1}{2}(DE - AB))^2} = \sqrt{(\frac{1}{2})^2 - (\frac{1}{2}(\sqrt{2} - \frac{\sqrt{2}}{2}))^2} = \frac{\sqrt{2}}{4} . The area of trapezoid A D E B ADEB is then A A D E B = 1 2 ( A B + D E ) h 1 = 1 2 ( 2 2 + 2 ) 2 4 = 3 8 A_{ADEB} = \frac{1}{2}(AB + DE)h_1 = \frac{1}{2}(\frac{\sqrt{2}}{2} + \sqrt{2})\frac{\sqrt{2}}{4} = \frac{3}{8} .

By the Pythagorean Theorem on B E G \triangle BEG , B G = B E 2 + E G 2 = ( 1 2 ) 2 + ( 1 6 ) 2 = 10 6 BG = \sqrt{BE^2 + EG^2} = \sqrt{(\frac{1}{2})^2 + (\frac{1}{6})^2} = \frac{\sqrt{10}}{6} . Also by the Pythagorean Theorem, the height of trapezoid A F G B AFGB is h 2 = B G 2 ( 1 2 ( F G A B ) ) 2 = ( 10 6 ) 2 ( 1 2 ( 2 2 2 ) ) 2 = 22 12 h_2 = \sqrt{BG^2 - (\frac{1}{2}(FG - AB))^2} = \sqrt{(\frac{\sqrt{10}}{6})^2 - (\frac{1}{2}(\sqrt{2} - \frac{\sqrt{2}}{2}))^2} = \frac{\sqrt{22}}{12} . The area of trapezoid A F G B AFGB is A A F G B = 1 2 ( A B + F G ) h 2 = 1 2 ( 2 2 + 2 ) 22 12 = 11 8 A_{AFGB} = \frac{1}{2}(AB + FG)h_2 = \frac{1}{2}(\frac{\sqrt{2}}{2} + \sqrt{2})\frac{\sqrt{22}}{12} = \frac{\sqrt{11}}{8} .

By the distance formula, G C = 10 3 GC = \frac{\sqrt{10}}{3} , and by symmetry, F C = G C = 10 3 FC = GC = \frac{\sqrt{10}}{3} . By Heron's Formula the area of G F C \triangle GFC is A G F C = 11 6 A_{\triangle GFC} = \frac{\sqrt{11}}{6} .

The total surface area is S = A B E G + A A D F + A E H C G + A D H C F + A E D H + A A D E B + A A F G B + A G F C = 1 24 + 1 24 + 1 3 + 1 3 + 1 2 + 3 8 + 11 8 + 11 6 = 39 + 7 11 24 S = A_{\triangle BEG} + A_{\triangle ADF} + A_{EHCG} + A_{DHCF} + A_{\triangle EDH} + A_{ADEB} + A_{AFGB} + A_{\triangle GFC} = \frac{1}{24} + \frac{1}{24} + \frac{1}{3} + \frac{1}{3} + \frac{1}{2} + \frac{3}{8} + \frac{\sqrt{11}}{8} + \frac{\sqrt{11}}{6} = \frac{39 + 7\sqrt{11}}{24} . Therefore, a = 39 a = 39 , b = 7 b = 7 , c = 11 c = 11 , d = 24 d = 24 , and a + b + c + d = 81 a + b + c + d = \boxed{81} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...